Overconfidence on Retail Stock Investor Investment Decisions in Stockbit: Moderating Role of Financial Literacy - Fitrah Diraya Sutardi; Tiar Lina Situngkir; Arif Fadilla (STIE AMKOP, 2026)
This study aims to determine how financial literacy moderates the correlations between those characteristics and how overconfidence influences stock investment decisions. The study focused on retail Stockbit stock investors who have made stock investments in the past or are presently doing so. This study employed a quantitative methodology. Using specific criteria aligned with the study's objectives, questionnaires were used to collect primary data from respondents selected through purposive sampling. A final sample of 260 responders was obtained using this process. The two stages of data analysis were simple linear regression and moderation interaction testing using Andrew F. Hayes' PROCESS Macro, which was backed by Microsoft Excel and SPSS software. The results show that overconfidence has a major influence on stock investment decisions. Furthermore, financial literacy does not moderate the relationship between overconfidence and stock investment decisions. These findings imply that Stockbit's retail stock investors' investment behavior is influenced by overconfidence bias, regardless of their level of financial literacy. Keywords: overconfidence; financial literacy; stock investment decisions; stockbit.